2017
DOI: 10.1016/j.jmii.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream infections in pediatric patients with acute leukemia: Emphasis on gram-negative bacteria infections

Abstract: Neutropenia was the major risk factor of BSIs in pediatric leukemic patients. BSIs of GNB were associated with severe neutropenia, systemic inflammatory responses, and high mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 21 publications
2
28
2
1
Order By: Relevance
“…The high rate of shock occurred because our patients were neutropenic children and adolescents, and their conditions deteriorated rapidly. Another study of E. coli bacteremia in pediatric patients with acute leukemia showed a higher shock/hypotension rate of 71% [22]. The multivariate analysis demonstrated that RDW level (> 15%) and WBC count (< 300/mm 3 ) were risk factors for shock.…”
Section: Discussionmentioning
confidence: 90%
“…The high rate of shock occurred because our patients were neutropenic children and adolescents, and their conditions deteriorated rapidly. Another study of E. coli bacteremia in pediatric patients with acute leukemia showed a higher shock/hypotension rate of 71% [22]. The multivariate analysis demonstrated that RDW level (> 15%) and WBC count (< 300/mm 3 ) were risk factors for shock.…”
Section: Discussionmentioning
confidence: 90%
“…Bloodstream infection (BSI) was defined as a positive isolate in a blood culture that was associated with clinical findings. [ 1 ] BSI is usually a serious complication of a malignant hematologic disease and can be a cause of death. Blood cultures and drug sensitivity tests were used to establish a direct basis for blood infections.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 80.2% of episodes occurred in the neutropenic period and 77.8% of them had severe neutropenia. In the study by Kuo et al neutropenia was identified in 83.5% of BSI episodes; 73% of them had severe neutropenia [11]. Responsible pathogens may vary between centers according to the use of empirical intravenous antibiotics and the rate of compliance with antisepsis procedures.…”
Section: Discussionmentioning
confidence: 98%